2022
DOI: 10.3389/fpubh.2022.899808
|View full text |Cite
|
Sign up to set email alerts
|

Health Professionals' Knowledge, Attitude and Practices Regarding COVID-19 in Dessie City, Northeast Ethiopia: A Facility-Based Cross-Sectional Study

Abstract: BackgroundKnowledge and attitudes are among the key drivers of social behavioral change. We assessed employed health professionals' (HPs) knowledge, attitude, and practice regarding COVID-19 in Dessie city, northeast Ethiopia.MethodsA facility-based cross-sectional study was conducted among 419 HPs working at Dessie city from 17 to 21 May 2020. The data were collected using a self-administered structured questionnaire. Knowledge, attitude, and practice are measured using 19, 16, and 8 questions, respectively. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
0
3

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 13 publications
0
0
3
Order By: Relevance
“…This could be due to the ineffective implementation of available COVID‐19 manuals, guidelines, rules, and regulations. This finding was low compared to a study conducted in 2020 48,49 . Conversely, the prevention practice against the COVID‐19 among healthcare workers in this study was higher than that reported in Ethiopia 50,51 .…”
Section: Discussioncontrasting
confidence: 90%
See 2 more Smart Citations
“…This could be due to the ineffective implementation of available COVID‐19 manuals, guidelines, rules, and regulations. This finding was low compared to a study conducted in 2020 48,49 . Conversely, the prevention practice against the COVID‐19 among healthcare workers in this study was higher than that reported in Ethiopia 50,51 .…”
Section: Discussioncontrasting
confidence: 90%
“…This finding was low compared to a study conducted in 2020. 48 , 49 Conversely, the prevention practice against the COVID‐19 among healthcare workers in this study was higher than that reported in Ethiopia. 50 , 51 This might be caused by disparities in access to the most recent information, instructions, and manuals.…”
Section: Discussioncontrasting
confidence: 61%
See 1 more Smart Citation